Gambaran Pengetahuan Siswi Kelas X dan XI Terhadap Swamedikasi Menggunakan Obat Herbal Kunyit Dan Asam Jawa Untuk Keluhan Dismenorea Di SMKN “X” Di Kabupaten Kuningan - Atik Kusmiati; Herliningsih Herliningsih (Jurnal Farmaku (Farmasi Muhammadiyah Kuningan), 2018)
This research was conducted to know the knowledge of female students of class X and XI toward self-medication (swamedication) using herbal medicine (medicinal herb) of turmeric and tamarind for complaints of dysmenorrheal in SMKN "X" in Kuningan. The research design used descriptive quantitative research. The data was collected by using instrument in the questionnaire form. The questionnaire that was used consisted of two questionnaires namely questionnaires in the form of statements and questions, both questionnaires use closed questionnaires using Guttman scales for a firm and consistent answer that is true and false, yes and no. The first questionnaire consisted of eight items of favorable and unfavorable statements representing 3 indicators of herbal medicines, namely general knowledge of herbal medicine, the benefits of using herbal medicine, the things that must be considered in the use of herbal medicine. The second questionnaire consisted of eight items of questions, which consists of three indicators that representing knowledge swamedication using herbal medicine turmeric and tamarind for complaints dysmenorrhoea, that is knowledge of dysmenorrhoea, plant turmeric, tamarind and its’ benefits, advantages of turmeric and tamarind. The data analysis technique that used is by using formula percentage. Hypothesis is done by using SPSS version 21. And it is concluded that the knowledge of class X and XI students on swamedication using herbal medicine turmeric and tamarind in SMKN "X" in Kuningan is categorized good or understood. Hypothesis test results showed that H1 accepted, which means that students have the knowledge toward swamedication using herbal medicine turmeric and tamarind to complaints dysmenorrhoea.